Perceived Leadership Integrity in the Manufacturing Industry - McCann, Jack (Journal of business ethics, 2013)
Ethics is a significant issue among those in leadership positions, especially since the ethical corporate scandals of the 1970s followed by corporate scandals in the 1980s and the S&L scandals of the 1980s and 1990s and most recently the global financial crisis of 2006–2009. The purpose of this research was to measure the perceived leadership integrity in today’s manufacturing environment, since the global financial crisis, as perceived by their employees. This study included 7,233 manufacturing employees in the United States. A total of 66 surveys were used to calculate data for this study. The Perceived Leader Integrity Scale (PLIS) was used to collect data from respondents that included demographic questions. The research addressed the following question: To what degree are leaders in the manufacturing industry considered “low ethical,” “moderate ethical,” and “high ethical” on the PLIS?